2020
DOI: 10.1038/s41419-020-02919-7
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 regulates Eg5 distribution within the mitotic spindle and modulates the cytotoxicity of Eg5 inhibitors

Abstract: The heat shock protein 70 (HSP70) is a conserved molecular chaperone and proteostasis regulator that protects cells from pharmacological stress and promotes drug resistance in cancer cells. In this study, we found that HSP70 may promote resistance to anticancer drugs that target the mitotic kinesin, Eg5, which is essential for assembly and maintenance of the mitotic spindle and cell proliferation. Our data show that loss of HSP70 activity enhances Eg5 inhibitor-induced cytotoxicity and spindle abnormalities. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…The numbers of cells with indicated spindle types were counted using a Zeiss Axioplan 2 Imaging MOT fluorescence microscope. Mitotic spindles at prophases, prometaphases, and metaphases, judged as described previously 64 , 70 , were counted as normal spindles. Multipolar spindle, monopolar spindle, disorganized spindle, and bipolar spindle with misaligned chromosomes were judged as mitotic spindle abnormalities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of cells with indicated spindle types were counted using a Zeiss Axioplan 2 Imaging MOT fluorescence microscope. Mitotic spindles at prophases, prometaphases, and metaphases, judged as described previously 64 , 70 , were counted as normal spindles. Multipolar spindle, monopolar spindle, disorganized spindle, and bipolar spindle with misaligned chromosomes were judged as mitotic spindle abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of mdivi-1 on the instability of microtubules was examined by cold treatment assay 71 . MDA-MB-231 cells were treated with mdivi-1 as indicated and subjected to 10 min cold treatment, followed by immunostaining, as described previously 64 , 70 . Mitotic cells with microtubule remnants at the spindle pole (pole-MT) were counted; a decrease in number indicates microtubule instability.…”
Section: Methodsmentioning
confidence: 99%
“…As chaperone protein complexed with mitotic kinases can modulate their activity during the progression of cell-cycle [ 57 , 58 ], we next tested whether centrosome-targeting of MPS1 was dependent on the presence of GRP75. Confocal checking the association of GRP75 and MPS1 at centrosome showed that these two targets were unable to simultaneously localize at centrosomes in GRP75-KD and phosphorylation-inactivation (T62A/S65A) cell.…”
Section: Resultsmentioning
confidence: 99%
“…S10, S11) suggests that GRP75 is also required for centrosome duplication and mitotic checkpoint response. Additionally, centrosome is a highly unstable macromolecular complex and Hsp70–Hsp90 chaperone machinery is essential to maintain centrosome integrity for cell-cycle progression [ 57 , 58 ]. Thus, centrosome-recruiting of GRP75 from S- to M-phase (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether RAE1 could be a therapeutic target, we performed a comprehensive analysis of 276 genes encoding microtubule‐regulating proteins 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 using TCGA data and evaluated their potential efficacy as a therapeutic target. We calculated the fold change in mRNA expression of each gene in tumor tissues compared to normal tissues, the correlation between mRNA expression and DNA copy number, and whether the high expression group was associated with poor prognosis.…”
Section: Resultsmentioning
confidence: 99%